Influence of Denture Cleansers on the Retention Loss of Attachment Systems Retained Implant Overdenture - AlRumaih, Hamad S.; Albarrak, Alhanouf A.; AlMedaires, Muneera; Alsulaiman, Ahmed A.; Baba, Nadim Z.; Alshahrani, Faris A.; Alqarawi, Firas K.; Al-Dulaijan, Yousif A.; Alzoubi, Fawaz; Alhumaidan, Abdulkareem A.; Gad, Mohammed M. (International Journal of Biomaterials, 2023)
Background. This study aimed to evaluate the effects of different denture cleansing solutions (DCSs) on the retention of Locator and Locator R-Tx attachment systems of implant retained overdentures (IRO). Methods. Two part acrylic resin blocks were fabricated, upper part contained metal housing and plastic inserts and lower part contained implant analogs and abutments. Eighty pink plastic inserts (40/attachment, 10/solution) were immersed in Corega, Fittydent, sodium hypochlorite, and water for a time simulating upto 1-year of clinical usage. Acrylic blocks were held on a universal testing machine for a pull-out test to record the dislodgement force. Measurements were conducted after 6 months (T1) and 12 months (T2). One-way ANOVA followed by Tukey’s HSD test was used to analyze the results (α = 0.05). Results. For both attachments, retention significantly decreased after immersion in different solutions at T2 P<0.001. Locator R-Tx attachment in NaOCl showed a significant decrease in retention compared with other solutions at T1. At T2, there was a significant decrease in retention for all DCS compared with water P<0.001. Locator R-TX showed higher retention values per solution compared to Locator attachment P<0.001. In terms of retention loss %, NaOCl recorded the highest (61.87%) loss, followed by Corega (55.54%) and Fittydent (43.13%), whereas water demonstrated the best retention (16.13%) in both groups. Conclusion. Locator R-TX has better retention with different DCS immersion. The loss of retention varied with different types of DCS and NaOCl recorded the highest retention loss. Therefore, denture cleanser selection must be guided by the type of IRO attachment.